PENGEMBANGAN FLIPBOOK BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK FASE E SMA - Reza, Hazim Saputra Filia (Jurnal Edukasi dan Penelitian Matematika, 2025)
In the preliminary analysis, it was found that the mathematical literacy skills of phase E students of SMA Negeri 13 Padang were still relatively low due to the lack of optimal learning media available such as teaching materials that were still limited. This study aims to produce a flipbook based on Realistic Mathematics Education to improve the mathematical literacy skills of phase E high school students who are valid and practical. This development research uses Plomp's development model which consists of three stages, namely preliminary research, prototyping or development phase, and assessment phase. In preliminary research, needs analysis, curriculum analysis, concept analysis, and learner analysis were conducted. In the development phase, designing flipbooks based on Realistic Mathematics Education, then conducting formative evaluation, namely self evaluation, expert review, one to one evaluation, and small group evaluation. The flipbook was validated by three experts, while the practicality of the flipbook was determined by 36 students in phase E of SMA Negeri 13 Padang, with data collection through observation, interviews, and filling out questionnaires. The results showed that the Realistic Mathematics Education-based flipbook was categorized as “Very Valid” with a validation level of 89.28% by experts based on aspects of presentation, content feasibility, language, and graphics. In addition, flipbooks are also categorized as “Very Practical” with a practicality level of 95.60% by students based on aspects of ease of use, time efficiency, attractiveness, ease of understanding, and the benefits of flipbooks.Keywords– Flipbook, Realistic Mathematics Education, Kemampuan Literasi Matematis, Perbandingan Trigonometri, Blended Learning